TRADITION, CRAFTSMANSHIP AND LOWER CIRCUIT OF THE URBAN ECONOMY IN THE LAND OF BOBBIN LACE - Almeida, Robson dos Santos (Geosaberes; Vol 14 (2023)DO - 10.26895/geosaberes.v14i0.1256, 2023)
Due to its artisanal tradition, the municipality of São Sebastião-AL is known as “The land of bobbin lace”. Using participant research, communicative relationships were established with the lacemakers of São Sebastião-AL and, through this information, a profile of bobbin lace production in the municipality was drawn, observing the materials used, the work, the form of organization , products and marketing. Paying attention to this last item mentioned, this work also focuses on the relationship between the lacemakers salomeenses and their main buyer, the businesswoman Martha Medeiros. Thus, the work provides an overview of the reality of lacemakers in the city of São Sebastião-AL, noting that the work is done almost predominantly by women aged over 50 years - most of them already retired -, and found in the production of income bobbin an extra source of savings. A group of women who are faced with a lack of encouragement, appreciation and health issues, aspects that have led to a decrease in the number of active lacemakers in the city and to a concern on their part that one day the tradition will end in São Sebastião-AL.